2021
DOI: 10.3892/ijmm.2021.5024
|View full text |Cite
|
Sign up to set email alerts
|

Effect and mechanism of propranolol on promoting osteogenic differentiation and early implant osseointegration

Abstract: The present study aimed to investigate the effect of β-receptor blocker propranolol on early osseointegration of pure titanium implants and the underlying molecular regulatory mechanisms. An implant osseointegration model using the tibial metaphysis of New Zealand rabbits was established. The rabbits were divided into control and low-, medium-and high-dose propranolol groups. The formation of implant osseointegration was detected by X-ray scanning. Mesenchymal stem cells (MScs) and osteoblasts (OBs) were isola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 58 publications
(76 reference statements)
0
5
0
Order By: Relevance
“…Butax treatment may relieve sympathetic suppression of mechanically stimulated osteoblast differentiation in vivo, as predicted by the findings of in vitro studies using PRO ( 51 ) and ISO ( 52 ) to manipulate β‐adrenergic activity in osteoblastic cultures. Mechanically stimulated calcium signaling is known to enhance osteoblast proliferation and differentiation through PI3K/AKT, ERK/Elk1, and CaMK/CREB signaling pathways.…”
Section: Discussionmentioning
confidence: 86%
“…Butax treatment may relieve sympathetic suppression of mechanically stimulated osteoblast differentiation in vivo, as predicted by the findings of in vitro studies using PRO ( 51 ) and ISO ( 52 ) to manipulate β‐adrenergic activity in osteoblastic cultures. Mechanically stimulated calcium signaling is known to enhance osteoblast proliferation and differentiation through PI3K/AKT, ERK/Elk1, and CaMK/CREB signaling pathways.…”
Section: Discussionmentioning
confidence: 86%
“…Wu et al. [ 43 ] discovered that the β-receptor blocker propranolol increased the expression levels of osteogenesis-associated genes in New Zealand rabbits, such as bone morphogenetic protein (BMP2), RUNX family transcription factor (RunX2), collagen (COL-1), and osteocalcin (OCN). Consequently, this augmentation promotes the osteogenic differentiation of mesenchymal stem cells (MScs) and OBs.…”
Section: Discussionmentioning
confidence: 99%
“…Past research has established the presence of β2-adrenergic receptor (AR) on the surface of human osteoblasts (OBs), and it has been suggested that β2-AR agonists could potentially hinder the proliferation of OBs 40 . Wu et al 41 discovered that the β-receptor blocker propranolol increased the expression levels of osteogenesis-associated genes, such as bone morphogenetic protein (BMP2), RUNX family transcription factor (RunX2), collagen (COL-1), and osteocalcin (OCN). Consequently, this augmentation promotes the osteogenic differentiation of mesenchymal stem cells (MScs) and OBs.…”
Section: Discussionmentioning
confidence: 99%